1996
DOI: 10.1007/bf00044458
|View full text |Cite
|
Sign up to set email alerts
|

Farmer participation in reforestation incentive programs in Costa Rica

Abstract: Reforestation programs are a common policy response among developing country governments in the tropics attempting to deal with environmental and economic problems caused by widespread deforestation. The objective of this paper is to examine participation by smalland medium-sized farms in two reforestation programs undertaken in recent years by one country, Costa Rica, which has been at the forefront of developing country environmental protection efforts. Analysis of a survey of 243 program participants and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 24 publications
4
46
0
4
Order By: Relevance
“…The influence of age on participation in forestry activities is not clear. Whilst some of the researches found that age had no influence on forest management [30,33] , other researcher reported that age is an important variable in explaining participation [3] . Household size influence participation in forestry [32,13] .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of age on participation in forestry activities is not clear. Whilst some of the researches found that age had no influence on forest management [30,33] , other researcher reported that age is an important variable in explaining participation [3] . Household size influence participation in forestry [32,13] .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…There are many causes of forest degradation that include converting forests to land agricultural, over harvesting of industrial wood and fuelwood, overgrazing, insect, pests and diseases, fire and extreme climatic events such as storms [14] . Based on mentioned subjects reforestation programs are a common policy response among developing country governments in the tropics attempting to deal with environmental and economic problems caused by widespread deforestation [30] . It is widely argued that devolution of natural resource management is the most viable option for ecological and economic sustainability of the natural resources [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Tenure variables were significant in 72% of agroforestry adoption studies that included them, with greater tenure security being consistently associated with greater adoption (Pattanayak et al, 2003). In Costa Rica, both Thacher et al (1997) and Zbinden and Lee (2005) found tenure-related variables to be highly significant in explaining participation in the country's PES program and its predecessors. Programs that require adoption of new practices may also face technical or financial constraints.…”
Section: Constraints To the Participation Of Poor Households In Pes Pmentioning
confidence: 99%
“…Tenure variables were significant in 72% of agroforestry adoption studies that included them, with greater tenure security being consistently associated with greater adoption (Pattanayak et al, 2003). Thacher et al (1997) and Zbinden and Lee (2005) found tenure-related variables to be highly significant in explaining participation in Costa Rica's PES program and its predecessor programs.…”
mentioning
confidence: 99%
“…Access to extension was found to significantly affect agroforestry adoption in 90% of studies that included it (Pattanayak et al, 2003), including two studies in Costa Rica (Thacher et al, 1997;Zbinden and Lee, 2005).…”
mentioning
confidence: 99%